Does platelet/ lymphocyte ratio a predictor of CD34+ peripheral blood stem cell yield in the healthy donors mobilized with GCSF? - Gokgoz, Zafer (POLTEKKES KEMENKES YOGYAKARTA, 2020)
This research aimed to determine whether there is a correlation between platelet/lymphocyte ratio the number of collected CD34+ stem cells. This retrospective study included 94 adult related stem cell donors who were healthy and volunteer by screening their files between the years 2016 and 2018. All donors were mobilized using 2.5 mcg/kg lenograstim or filgrastim and underwent peripheral stem cell apheresis. Complete blood counts were tested at baseline before G-CSF administration (pre–G-CSF), and before PBSC collection after mobilization with G-CSF administration. The patients were divided into two groups as aged below and over 50 years old. From these comparative data, only BMI value of the group aged below 50 years was statistically significantly lower than the other group, whereas no statistically significant difference was found between the groups in terms of other parameters. The numbers of the collected CD34+ stem cells of both age groups were similar, and no significant difference was found. The values of platelet/lymphocyte ratio, early measurement of CD34+ stem cells and the amount of the collected CD34+ stem cells of both groups at the first and second days of the procedure were found similar. This research show that a high platelet count and consequently, a high platelet/lymphocyte ratio may be correlated with the number of collected CD34+ stem cells but our hypotheses revealed insignificant outcomes.